2017
DOI: 10.1002/app.45850
|View full text |Cite
|
Sign up to set email alerts
|

Maximum actuation strain for dissipative dielectric elastomers with simultaneous effect of prestretch and temperature

Abstract: A dielectric elastomer can generate giant deformation by the voltage actuation, but the deformation is often hindered by the electromechanical instability and “snap‐through deformation,” which may lead to electrical breakdown. In this study, for the first time, the mathematical model is established for dissipative dielectric elastomers in the dynamic model with simultaneous effect of prestretch and temperature in order to achieve maximum actuation strain. The deformation of the dissipative dielectric elastomer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Although most DE researches did not consider the temperature parameter, it affects also the elastic modulus and dielectric constant of DE (Jean-Mistral et al, 2010; Vu-Cong et al, 2013b). Deng et al (2018) studied the effect of constant and ramp voltage with the optimum temperature, pre-tension, and voltage combination that achieved the maximum driving strain. Sheng et al analyzed various failure modes and the stability of DE with a model of the temperature effect.…”
Section: Introductionmentioning
confidence: 99%
“…Although most DE researches did not consider the temperature parameter, it affects also the elastic modulus and dielectric constant of DE (Jean-Mistral et al, 2010; Vu-Cong et al, 2013b). Deng et al (2018) studied the effect of constant and ramp voltage with the optimum temperature, pre-tension, and voltage combination that achieved the maximum driving strain. Sheng et al analyzed various failure modes and the stability of DE with a model of the temperature effect.…”
Section: Introductionmentioning
confidence: 99%
“…It was also reported that the natural frequency increases at lower temperatures (natural frequency at 273 K is 29.53 rad s −1 while that is 16.34 rad s −1 at 333 K) when tested under sinusoidal nominal electric fields. According to Deng et al [21], the maximum actuation strain enhances with the increase of the voltage but drops with the increase of prestretch and temperature in the area of the best combined conditions under the constant voltage stimulation. However, under the ramping voltage condition, the maximum actuation strain increases with the decrease of prestretch, ramping rate, and temperature within the best combined conditions areas.…”
Section: Introductionmentioning
confidence: 99%